DESIGN CONSIDERATIONS IN THE FORMING OF AUTOMOBILE PARTS - ADEGBUYI, Patrick.Adebisi. Olusegun (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Manufacturing is the main stay of any Nations economy, and the process of manufacturing starts with the production of machine components which is made possible through putting ideas into design and a method of manufacture is determined. This work presents the design of a machine for forming the Back- Plate of a brake pad through stamping and punching. The tools used are called dies and are made having the specific shape that needs to be formed.